2020
DOI: 10.1097/md.0000000000021412
|View full text |Cite
|
Sign up to set email alerts
|

Association between dementia and psychiatric disorders in long-term care residents

Abstract: We examine the relationship between dementia and psychiatric disorder diagnoses among long-term care residents in nursing homes across the state of Rhode Island (RI), USA. Observational clinical study. Two hundred fifty-five residents with and without the diagnosis of dementia were included in this study. Prevalence analysis was used to elucidate information on psychiatric disorders in the overall cohort, and among residents with dementia. Questions from the quality of life que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Mansbach et al [ 47 ] used the Brief Anxiety and Depression Scale to assess the prevalence of depression among long-term care residents in America, and the result showed that the prevalence was 54.5%. However, another study conducted in Rhode Island, USA suggested that only 28.6% of all residents in long-term care facilities suffered from depression [ 48 ]. Wongpakaran et al [ 49 ] found that the prevalence of depression among institution-dwelling older adults was 23.5% in northern Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…Mansbach et al [ 47 ] used the Brief Anxiety and Depression Scale to assess the prevalence of depression among long-term care residents in America, and the result showed that the prevalence was 54.5%. However, another study conducted in Rhode Island, USA suggested that only 28.6% of all residents in long-term care facilities suffered from depression [ 48 ]. Wongpakaran et al [ 49 ] found that the prevalence of depression among institution-dwelling older adults was 23.5% in northern Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…a sex ratio (M/F) of 0.89. This female predominance is noted by several studies [3,4]. In its report on the impact of mental and behavioral disorders in 2001, the WHO states that mental disorders are on average more prevalent in women than in men [1], and in correlation with the high age of the respondents, the significant proportion of women can be explained by their longer life expectancy [5].…”
Section: Discussionmentioning
confidence: 96%
“…Thus far, nondrug interventions have been preferred as they are effective for reducing mild to moderate symptoms of depression in this patient population. Popular interventions used include animal therapy, cognitive stimulation, exercise and social interaction, massage therapy, reminiscence therapy, occupational therapy, multidisciplinary care, and environmental modification 48,50 . Data regarding treatment of major depression in patients with neurocognitive disorders are mixed 48,50,51 …”
Section: Neurologic Disorders That Cause Mood Disordersmentioning
confidence: 99%
“…Popular interventions used include animal therapy, cognitive stimulation, exercise and social interaction, massage therapy, reminiscence therapy, occupational therapy, multidisciplinary care, and environmental modification. 48,50 Data regarding treatment of major depression in patients with neurocognitive disorders are mixed. 48,50,51 Headache Headaches, more specifically migraines, have high rates of comorbidities with mood disorders, including depressive disorder and bipolar disorder.…”
Section: Multiple Sclerosismentioning
confidence: 99%